Productivity potentials of rubberseed - Nadarajapillai N; Wijewantha Ronald T
The productivity potentials of rubber seed in Ceylon is reviewed. All the tallow presently imported for the manufacture of soap could be replaced by rubber seed oil. The rubber seed cake can be used as a fertilizer and as animal feed. The cake is rich in protein abd its nutritive value is comparable to that of linseed cake abd cotton seed cake. The HCN content of the cake can be reduced by reducing the moisture content of the kernel and by increasing the period of storage. Experiments have shown that adequately dried kenel could be kept without ab appreciable deterioration up to six months if humidity during storage period is kept under control. The joint project of Rubber Research Institute of Ceylon with Lever Brothers (Ceylon) limited for studying the commercial possibility and economics of oil extraction is also described.
Keywords: Productivity; Rubber seed